Investigation of Quality-of-Service (QoS) issue in IP networks - Lim, Peng Koon. (2008)
This dissertation investigates the issues of Quality of Services (QoS) in IP network. This dissertation examines the various issues of QoS techniques and architectures, and strives to illustrate an End-to-End QoS model by integrating 3 of the IETF’s proposed QoS service models, which are IntServ, DiffServ and MPLS.